Does education reduce wage inequality? Quantile regression evidence from 16 countries - Martins, Pedro S. (2021)
Quantile regression estimates of returns to education are used to address the relation between schooling and wage inequality. Empirical evidence for male workers from 16 countries for the mid 1990s suggests a robust stylised fact: Returns to schooling are higher for the more skilled individuals, conditional on their observable characteristics. This suggests that schooling has a positive impact upon within-levels wage inequality. Factors such as over-education, ability – schooling interactions and school quality or different fields of study may be driving this result. D 2003 Elsevier B.V. All rights reserved.